2018
DOI: 10.1130/g39663.1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotope evidence for transient marine-shelf oxidation during the Ediacaran Shuram Excursion

Abstract: The Ediacaran Shuram Excursion (SE) was a major negative δ13Ccarb excursion (to −12‰) thought to reflect significant atmospheric-oceanic oxidation, although direct evidence is limited. Here, we model changes in seawater sulfate concentrations ([SO42−]sw) during the SE by using paired S-isotope data of cogenetic sedimentary pyrite and carbonate-associated sulfate from the Ediacaran Doushantuo Formation (South China), making independent calculations for inner-shelf and upper-slope sections. Our results show a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 26 publications
5
48
0
Order By: Relevance
“…Despite the inability to use Tl isotopes to directly constrain ocean oxygenation, our interpretation of increased ocean oxygenation at the EN3a to EN3b transition is consistent with previously reported evidence for an oxygenation event during this time, which was based on globally enhanced continental weathering (Li et al, ; Sawaki et al, ), elevated marine sulfate concentrations and decreased sulfur isotope composition (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ), elevated marine iodate concentrations observed in a range of global depositional settings (Hardisty et al, ), and a positive U isotope excursion (Kendall et al, ; Zhang et al, ). Although spatially heterogeneous, paired δ 13 C and δ 34 S records show coincident negative excursions interpreted to represent an event that oxidized large dissolved organic carbon and sulfide pools in the deep oceans (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ; Shi et al, ). Coincident with the Shuram NCIE records, I/(Ca + Mg) ratios from three separate paleocontinents have been shown to shift to higher values indicating the presence of locally oxic water columns in these shallow carbonate environments (Hardisty et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the inability to use Tl isotopes to directly constrain ocean oxygenation, our interpretation of increased ocean oxygenation at the EN3a to EN3b transition is consistent with previously reported evidence for an oxygenation event during this time, which was based on globally enhanced continental weathering (Li et al, ; Sawaki et al, ), elevated marine sulfate concentrations and decreased sulfur isotope composition (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ), elevated marine iodate concentrations observed in a range of global depositional settings (Hardisty et al, ), and a positive U isotope excursion (Kendall et al, ; Zhang et al, ). Although spatially heterogeneous, paired δ 13 C and δ 34 S records show coincident negative excursions interpreted to represent an event that oxidized large dissolved organic carbon and sulfide pools in the deep oceans (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ; Shi et al, ). Coincident with the Shuram NCIE records, I/(Ca + Mg) ratios from three separate paleocontinents have been shown to shift to higher values indicating the presence of locally oxic water columns in these shallow carbonate environments (Hardisty et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have suggested that the Shuram NCIE may be related to a period of ocean oxygenation (e.g., Fike et al, ; McFadden et al, ), resulting in the oxidation of a massive 13 C‐depleted dissolved organic carbon (DOC) reservoir in the deep ocean (Fike et al, ; Jiang et al, ; McFadden et al, ; Rothman, Hayes, & Summons, ). However, recent studies also suggested that local heterogeneous and transient oxygenation may have played a critical role in the expanded spatial heterogeneity of δ 13 C and δ 34 S excursions, not only from the Doushantuo Formation shales but also from carbonate platform regions worldwide during the Ediacaran (Li et al, ; Loyd et al, ; Osburn, Owens, Bergmann, Lyons, & Grotzinger, ; Shi et al, ). Therefore, the challenge is to establish the global extent of oceanic redox conditions for this period, which is important for understanding the connection between oceanic oxygenation and the radiation of Ediacaran‐type biota because the oldest Avalon Assemblage occurs in a deep‐water, volcaniclastic setting of the Avalon Zone of Newfoundland (Narbonne, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the cause of the rise of the Ediacara biota during the middle Ediacaran Period remains a subject of intensive debate. A temporal correlation with evidence for a major redox transition suggests that a profound ocean oxygenation event may have sparked this evolutionary event (Canfield, Poulton, & Narbonne, ; Fike, Grotzinger, Pratt, & Summons, ; McFadden et al, ; Shi et al, ). However, others have argued that the diversification of bilaterians may have been enabled by the evolution of key developmental toolkits (Erwin, ) and/or that the rise of eumetazoans was driven by positive ecological feedbacks (Butterfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the rise of the Ediacara biota, particularly the appearance of large, mobile, and morphologically complex animals, may have occurred either during (Darroch et al, 2018) or immediately following the SE (e.g., McFadden et al, 2008;Xiao et al, 2016). As such, it has been proposed that the SE represents an unprecedented ocean oxygenation event, which sparked the diversification of complex animals (Fike et al, 2006;McFadden et al, 2008;Shi et al, 2018;Wood et al, 2015). However, the extent of global ocean redox change across this critical interval is poorly constrained (Bristow and Kennedy, 2008).…”
mentioning
confidence: 99%
“…In other words, there is insufficient oxidant even in the modern atmosphere and oceans to remineralize enough organic matter to drive a -8‰ δ 13 C excursion for several million years. As a result, many authors have interpreted extreme negative anomalies as diagenetic artefacts, biased sampling of authigenic cements or as purely regional phenomena (Bristow & Kennedy, 2008;Derry, 2010;Grotzinger & Fike, 2011;Schrag et al, 2013;Li et al, 2017;Shi et al, 2018). However, such arguments appeal to an inexplicable sampling bias, whereby globally correlative isotopic signatures are presumed to be unrepresentative of the global carbonate sink.…”
Section: Introductionmentioning
confidence: 99%